“Gestión Administrativa y la rentabilidad de la Hacienda Bananera Margarita Dos del cantón Valencia, 2020”. - Acosta Morán, Gladys Yolanda (2022)
The present investigative work focuses on discovering the shortcomings in the administrative management of Margarita Dos Farm in the Valencia canton, through the application of research instruments. Likewise, it emphasizes the need to design an improvement plan for the administrative area aimed at optimizing costs, expenses; mitigate negative effects, through the optimal management of economic, material and human resources, seeking to offer a quality product to its local and international clients. To address the fulfillment of the objectives, this study established a methodology that requires the types of non-experimental, descriptive, bibliographic and quantitative field research, due to the identification of the study variables such as the presentation of numerical data that allowed determining the consistency of the results. The population corresponds to the administrative, accounting, production, quality and warehouse staff, giving a total of 49 people. Among the findings found, they mainly highlighted the lack of key elements in the phases of the administrative process, such as business objectives, manuals, process map, performance evaluation strategies, communication channels, which brings with it a weakness in management. The results of the application of the vertical analysis reflected that 88.32% of the Treasury's assets are concentrated in fixed assets and 73.19% of the liabilities correspond to the long-term bank loan account, the cost of sales constitutes 61.23% of the total income received and profit 27.33%. The horizontal analysis exposed negative variations in the asset and liability accounts in the 2019-2020 period. The NPV result corresponded to $632,014.81 and the Internal Rate of Return resulted in 74%, suggesting that the banana activity is viable. of the indicators denoted that the return on assets of Hacienda Margarita Dos Farm corresponds to 8%, reflecting that it is important to manage actions to improve the use of resources. The return on the gross margin corresponds to 39% having an operating deficiency. The primary and secondary information laid the foundations for the development of an improvement plan that acts on the stages of the administrative process: planning, organization, direction and control, which together allow improving the administrative management and resource management of Margarita Dos Farm.